The determinants regulating Toxoplasma gondii bradyzoite development - Pan, Ming; Ge, Ceng-Ceng; Fan, Yi-Min; Jin, Qi-Wang; Shen, Bang; Huang, Si-Yang (Frontiers in Microbiology, 2022)
Toxoplasma gondii is an obligate intracellular zoonotic pathogen capable of infecting almost all cells of warm-blooded vertebrates. In intermediate hosts, this parasite reproduces asexually in two forms, the tachyzoite form during acute infection that proliferates rapidly and the bradyzoite form during chronic infection that grows slowly. Depending on the growth condition, the two forms can interconvert. The conversion of tachyzoites to bradyzoites is critical for T. gondii transmission, and the reactivation of persistent bradyzoites in intermediate hosts may lead to symptomatic toxoplasmosis. However, the mechanisms that control bradyzoite differentiation have not been well studied. Here, we review recent advances in the study of bradyzoite biology and stage conversion, aiming to highlight the determinants associated with bradyzoite development and provide insights to design better strategies for controlling toxoplasmosis.